An IoT Guided Healthcare Monitoring System for Managing Real-Time Notifications by Fog Computing Services - Mani, Neel; Singh, Akhil; Nimmagadda, Shastri (2019)
Fog Computing is a new computing paradigm which is grown ever since it is being used. It is aimed at bringing the computations close to data sources from healthcare centers. IoT driven Fog Computing is developed in the healthcare industry that can expedite facilities and services among the mass population and help in saving billions of lives. The new computing platform, founded as fog computing paradigm may help to ease latency while transmitting and communicating signals with remote servers, which can accelerate medical services in spatial-temporal dimensions. The latency reduction is one of the necessary features of computing platforms which can enable completing the healthcare operations, especially in large-size medical projects and in relation to providing sensitive and intensive services. Reducing the cost of delivering data to the cloud is one of the research objectives.